Associations between the impact of access barriers and healthcare utilization among autistic adults in Germany - Shaden Suleiman (2024)
Background: Autistic adults report barriers to accessing and receiving healthcare, they also experience increased morbidity and mortality. Early planning and continuity of care are often emphasized, in the context of autism healthcare. In Germany, where the public health system is without financial barriers, studies on access to services are lacking. Person-centered interventions and systematic approaches are needed to address barriers at personal, professional, and systemic levels. This study will (1) compare current healthcare use of autistic adults to the general population in Germany, and (2) examine current barriers, clinical and socioeconomic factors affecting access and use of healthcare services, with the aim of informing future strategies for promoting equal care for autistic adults. Methods: Data from two cross-sectional studies were used, 288 autistic adult population samples were taken from the BarrierfreeASD (BASS) study along with an equal sample of adults from the German general population. Man-Whitney-U tests were calculated to compare the overall healthcare utilization of 5 services (general practitioner, mental health, dental health, ophthalmology, and emergency room visits) between both populations in Germany. Multivariate linear regression analyses were conducted to measure the influence of certain predictors on the healthcare utilization in the autistic population sample.